Approaches to the Formation of a Theoretical Model for the Analysis of Environmental and Economic Development - HOROBCHENKO, Denys; VORONENKO, Viacheslav (Journal of Environmental Management and Tourism, 2019)
The paper considers the influence of economic development factors on the state of the environment. The subject of the research is the processes of improving the sustainable development (SD). A theoretical model for analysis of environmental and economic development was worked out based on the existing methods and a more comprehensive presentation of information on the parameters of SD. Possibilities of achieving the Environmental Kuznets Curve as the conditions for the SD improvement are determined. A minimum condition to guarantee the nonavailability of deterioration in the SD was determined to overcome the point of maximum pollution. This point describes emissions of pollutants, taking into account the accumulation effect of the pollution, which can be observed from the moment of exceeding of the assimilation potential of the environment. Proposed approaches were applied to the development analysis relative to the environmental component, the case of carbon dioxide (CO2) emissions in Ukraine. Accordingly, Ukraine has a predominantly positive trend towards the SD relative to the environmental component. This trend is partly supported by predominant decrease in specific CO2 emissions per unit of output in the economy. On the other hand, there was a significant increase in the concentration of Ukraine's CO2 emissions in the atmosphere, despite the fact that the overall level of emissions has decreased. Therefore, overcoming the tendency of increase in the concentration of pollution requires a significant increase in the environmental effects of economic activities and the coordination of actions on the international level.